Construction mediation procedure 2002 (Thomas Telford, 2002)
This guide has been produced as a result of current best practice and its increasing use in dispute resolution, within the construction industry. It allows the parties to the dispute the freedom to explore ways of settling it with assistance of an independent impartial person - the Mediator.